Natur und Herrschaft : Analysen zur Physik der Macht - Jankrift, Kay Peter; Kagerer, Alexander; Kaiser, Christian, 1976-; Martín Romera, María Ángeles (De Gruyter, 2016)
"These conference proceedings address the shifting meanings, upheavals, invalidations, and validations linked to different perceptions of 'natural' rule. A focus is placed on widespread strategies for legitimizing and delegitimizing political office holders in pre-modern societies by means of recurrent recourse to 'natural' criteria marking an individual as distinct and qualified to lead"--Provided by publisher.